2018
DOI: 10.1002/pen.24816
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Production With Improved Functionality and Graphitization of Carbon Fine Fibers Developed from Sodium Chloride‐Polyacrylonitrile Precursors

Abstract: Fine polyacrylonitrile (PAN) fibers were produced through a scalable centrifugal spinning process. Sodium chloride (NaCl) was added to the PAN‐dimethylformamide solution to decrease the surface tension and consequently promote a decrease in fiber diameter while increasing the fiber output. The fiber preparation process involved the centrifugal spinning of the PAN‐based solution; developed fibers were stabilized in air at 240°C followed by carbonization at 800°C under a Nitrogen atmosphere. The addition of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This is in agreement with the literature, highlighting the conflict between the graphitization and the oxidation of the surface as it would affect the material conductivity and promote the formation of gaseous products that may block the active sites . For example, it was reported that both graphitization and functionality of the carbon fine fibers could be improved by adding NaCl precursor to the poly­(acrylonitrile–dimethyl­formamide) solution before the spinning process . Interestingly, the mild preferable oxidation is related to the neutral medium and the chosen potential window.…”
Section: Results and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with the literature, highlighting the conflict between the graphitization and the oxidation of the surface as it would affect the material conductivity and promote the formation of gaseous products that may block the active sites . For example, it was reported that both graphitization and functionality of the carbon fine fibers could be improved by adding NaCl precursor to the poly­(acrylonitrile–dimethyl­formamide) solution before the spinning process . Interestingly, the mild preferable oxidation is related to the neutral medium and the chosen potential window.…”
Section: Results and Discussionsupporting
confidence: 89%
“…59 For example, it was reported that both graphitization and functionality of the carbon fine fibers could be improved by adding NaCl precursor to the poly(acrylonitrile−dimethylformamide) solution before the spinning process. 61 Interestingly, the mild preferable oxidation is related to the neutral medium and the chosen potential window. The low oxidation thermodynamic potential of carbon (0.207 vs RHE) leads to carbon corrosion at relatively high anodic potential.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For polymer gel, lower adhesiveness is required to overcome the attractive force between gel and spinneret material. The adhesiveness calculation helps detect spinneret concentrations of cellulose gel of different concentrations [63]. Increasing solvent volatility also leads to increased polymer concentration [64].…”
Section: Factors Affecting Nanofiber Preparationmentioning
confidence: 99%
“…For example, Cheong et al synthesized SnO 2 /TiO 2 fiber nanostructures with a tubular morphology through electrospinning followed by calcination. As an anode material for lithium-ion batteries (LIBs), [18,19] SnO 2 /TiO 2 composite fibers demonstrated good cycling stability and have surpassed the theoretical capacity of commercial graphite anodes. The SnO 2 /TiO 2 tubular nanocomposite delivered a high reversible capacity of 900 mAh g À1 after 100 cycles at a current rate of 500 mA g À1 .…”
Section: Introductionmentioning
confidence: 99%